The Art and Science of Leadership in Learning Environments: Facilitating a Professional Learning Community across Districts - Hands, Catherine; Guzar, Katlyn; Rodrigue, Anne (Alberta Journal of Educational Research, 2016)
A professional learning community (PLC) is one of the most promising strategies for effecting change in educational practices to improve academic achievement and wellbeing for all students. The PLC facilitator’s role in developing and leading blended (online and face-to-face) PLCs with members from Ontario’s school districts was examined through a qualitative case study. The research involved a document analysis of 36 reflections from 6 facilitators, observations, and a 2-hour, open ended, semi-structured interview with 6 facilitation coaches associated with the Elementary Teachers’ Federation of Ontario. Facilitators shared leadership with PLC members to develop collaborative cultures, shared goals and artifacts, and guided them using dialogue and open-ended questioning to promote deep thinking, inquiry, and reflection. They scheduled meetings, set deadlines, monitored progress, and contacted members between meetings to encourage attendance. This research provides insight into the facilitators’ strategies for encouraging the production of shared goals and artifacts, and the organizational culture that promotes collaborative work. Une communauté d’apprentissage professionnelle (CAP) représente une des stratégies les plus prometteuses pour mettre en œuvre des changements dans les pratiques pédagogiques visant l’amélioration du rendement académique et le bienêtre de tous les élèves. Cette étude qualitative de cas a porté sur le rôle de l’animateur des CAPs dans le développement et la direction de CAPs mixtes (en ligne et en face à face) composées de membres de districts scolaires en Ontario. La recherche a impliqué une analyse de documents (36 réflexions de la part de 6 animateurs), des séances d’observation et une entrevue semi-structurée, à questions ouvertes et d’une durée de deux heures auprès de 6 formateurs en facilitation associés à la Fédération des enseignantes et des enseignants de l’élémentaire de l’Ontario. Les animateurs ont partagé le leadership avec les membres des CAPs de sorte à développer des cultures de collaboration, et des objectifs et des artéfacts partagés. De plus, les animateurs ont servi de guides pendant le dialogue et la présentation de questions ouvertes visant la réflexion approfondie et la recherche. Ils ont organisé des rencontres, établi les délais, suivi les progrès accomplis et, pour promouvoir la participation, contacté les membres entre les rencontres. Cette recherche offre des connaissances approfondies sur les stratégies qu’emploient les animateurs pour stimuler la production d’objectifs et d’artéfacts partagés ainsi que le développement d’une culture organisationnelle favorisant la collaboration.